Medical ceramic high-frequency electrotome
By adding conductive phases and toughened phases to the ceramic base phase, the problems of traditional high-frequency electrocutter adhesion and thermal damage are solved, and a more efficient and safer surgical process and better postoperative recover.
Patent Information
- Application Number
- CN202510038217.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2045-01-10
AI Technical Summary
Traditional stainless steel medical high-frequency electrocution knife is prone to adhesion and high-temperature thermal damage during use, which affects surgical efficiency and postoperative recovery.
Using composite ceramic materials, the hydrophobicity and electrical conductivity of the ceramic are regulated by adding conductive phases and toughening phases to the ceramic base phase with high mechanical properties, and the risk of thermal damage is reduced.
It effectively reduces adhesion during the surgery, reduces the risk of thermal damage, improves the safety and efficiency of the surgery, and promotes wound healing and scar recovery.
Smart Images

Figure FT_1 
Figure FT_2
Abstract
Description
Technical Field
[0001] The invention belongs to the field of medical equipment, and in particular relates to a medical ceramic high-frequency electric knife. Background Art
[0002] In the field of medical surgery, traditional stainless steel medical high-frequency electrosurgery has become an indispensable tool in surgery due to its wide application. However, this traditional electrosurgery has some significant problems in actual use. First, due to its material characteristics, the electrosurgery is prone to adhesion during use, which not only affects the efficiency of the operation, but may also cause unnecessary damage to the patient's tissue. Secondly, the risk of thermal damage caused by high-temperature operation is high, which may cause damage to surrounding healthy tissues and increase the risk of postoperative complications.
[0003] To solve these problems, researchers have proposed a variety of solutions, including lowering the operating temperature, installing ultrasonic assistive devices, and developing anti-adhesion coatings. Although these methods have alleviated the problem to a certain extent, they each have their limitations. Lowering the temperature may affect the efficiency of the electrosurgical unit, installing ultrasonic assistive devices will increase the difficulty of actual operation, and anti-adhesion coatings may degrade in performance at high temperatures and have limited durability.
[0004] The Chinese patent "A method for preparing conductive ceramics with controllable resistivity" (application number: 202411139412.3, publication number: CN202410916051.2) discloses a method for preparing aluminum oxide-titanium nitride ceramics. The conductive ceramics are prepared by low-temperature plasma ball milling mixing, gel molding and high-temperature sintering process, but the preparation process of this method is complicated and not suitable for large-scale production.
[0005] The Chinese patent "A method for conducting the surface of zirconia ceramics" (application number: 202110183207.7, publication number: CN 112979346 A) provides a method for preparing zirconia-based conductive ceramics. The method includes dry-pressing zirconia powder into a shape, applying a conductive slurry and drying it, and finally sintering it to make a conductive ceramic, but there is a problem of insufficient adhesion.
[0006] In view of this, this patent proposes a medical ceramic high-frequency electric knife. The electric knife is made of composite ceramic material, which utilizes the hydrophobicity of ceramic material to effectively reduce the adhesion phenomenon during surgery. In addition, the conductivity of the composite ceramic material is controllable, allowing the electric knife to operate at a lower temperature, thereby reducing the risk of thermal damage. The design of this new electric knife not only improves the safety and efficiency of surgery, but also provides better protection for patients' postoperative recovery. Summary of the invention
[0007] In view of the above problems, the present invention discloses a composite conductive ceramic suitable for high-frequency electric knife, and makes the following improvements to the existing electric knife, such as high thermal damage and easy adhesion: By adding a conductive phase to a ceramic matrix phase with high mechanical properties, such as alumina, zirconia, silicon nitride, etc., the AC impedance can be regulated and thermal damage can be reduced.
[0008] By adding conductive components with intrinsic hydrophobic properties such as titanium nitride, titanium carbide, titanium dioxide, etc., better hydrophobicity can be obtained without surface treatment, which plays an anti-adhesion role. The conductive properties of the composite conductive ceramic can be adjusted by adjusting the proportion of one or more conductive phases in the composite conductive ceramic, such as titanium nitride, titanium carbide, titanium dioxide, graphene, graphene oxide, and carbon nanotubes.
[0009] By adding toughening phases such as zirconium oxide, carbon fiber, carbon nanotubes, titanium carbonitride, etc., the mechanical properties of ceramic materials can be regulated and the grinding and sharpening properties of ceramics can be improved, which is beneficial for the preparation of high-frequency electric knives of various shapes such as ordinary surgical blades, spears, needles, crescents, etc.
[0010] Adding a small amount of mixed organic acid during sintering and combining it with a multi-step pressurization method can achieve better particle rearrangement in the low-temperature heating stage and better densification in the high-temperature sintering stage, thereby improving the mechanical properties of the material.
[0011] The sintering aid may be one or more of magnesium oxide, silicon oxide, and rare earth oxide.
[0012] Compared with the prior art, the present invention has the following beneficial effects: The present invention adjusts the proportion of the conductive phase in the composite conductive ceramic to reduce the conductivity and thermal damage compared with the traditional metal electric knife. By controlling the composition of the conductive phase, the in-situ hydrophobic property is achieved to reduce the adhesion phenomenon during the cutting process.
[0013] Compared with traditional metal electric knives, the low-adhesion and low-heat-damage medical ceramic high-frequency electric knife has better cutting quality, neatly breaks muscle fibers, and is conducive to wound scar recovery;
[0014] The ceramic sintering process uses the addition of mixed organic acids and multi-step pressurization method, and different pressure sintering at low and high temperatures, which helps the ceramic densification;
[0015] The mixed organic acid is a mixture of formic acid, acetic acid and citric acid, which has low cost and stable sintering quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is the staining result of pathological section of muscle tissue cut by stainless steel electric knife in comparative example 5.
[0017] Figure 2 This is the staining result of the pathological section of the muscle tissue cut by the ceramic electric knife in Example 1. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical solution and advantages of the present invention clearer, various aspects of the present invention will be described in detail in conjunction with specific embodiments. These specific embodiments are only used to illustrate the present invention and do not limit the protection scope and substantive content of the present invention. Example 1
[0019] The present invention provides an anti-adhesion medical high-frequency ceramic electric knife, and the specific preparation process includes: S1. Alumina ceramic powder, titanium nitride ceramic powder, magnesium oxide ceramic powder and 50nm zirconium oxide ceramic powder with a particle size of 500nm were mixed in a mass ratio of 58:40:6:6, anhydrous ethanol was added, ultrasonic stirring was performed for 15min, the mixture was put into a ball mill, and ball milling was performed for 20h. The ball-milled ceramic powder was dried and sieved with a 400-mesh sieve to obtain dry powder; S2. The dry powder was loaded into a mold, 0.3wt% of the mass of the dry powder was added to the mixed organic acid, and hot-pressed and sintered under nitrogen pressure at a nitrogen pressure of 0.2MPa; S3. Room temperature ~ 150℃, applied pressure is 80MPa, 150℃ ~ 600℃ applied pressure is 10MPa, 600℃ ~ 1700℃ applied pressure is 30MPa, heating rate is 10℃ / min, and the holding time at the highest temperature is 2h; S4. Process the sintered ceramic into the shape of a high-frequency electric knife, load the ceramic electric knife onto the high-frequency generator, and adjust the output power for electric cutting.
[0020] Effect verification: The prepared ceramic electric knife material was tested for flexural strength, contact angle, and AC impedance to evaluate the physical properties of the material. The results are shown in Table 1.
[0021] The model of the electrical cutting experiment was New Zealand white rabbit. The cutting of muscle tissue was observed by observing the postoperative pathological sections. The cutting results of Example 1 are shown in Figure 2 As shown, by scoring the cutting effect from 1 to 5, this is the best effect, with a score of 5; the cutting effect of Example 5 is the worst, as shown in Figure 1 As shown, the score was 1. The adhesion of the electrosurgical knife was judged by measuring the amount of tissue adhered after cutting, and the weight increased by 0.48%.
[0022] The effect test process of the electrosurgical material will not be described in detail below, and the specific results are shown in Table 1. Example 2
[0023] The present invention provides an anti-adhesion medical high-frequency ceramic electric knife, and the specific preparation process includes: S1. Alumina ceramic powder, titanium nitride ceramic powder, magnesium oxide ceramic powder and 50nm zirconium oxide ceramic powder with a particle size of 500nm were mixed in a mass ratio of 58:30:4:8, n-hexane was added, ultrasonic stirring was performed for 20min, the mixture was put into a ball mill, and ball milled for 24h. The ball-milled ceramic powder was dried and sieved with a 400-mesh sieve to obtain a dry powder; S2. The dry powder was loaded into a mold, 0.5wt% of the mass of the dry powder was added to the mixed organic acid, and hot-pressed and sintered under nitrogen pressure at a nitrogen pressure of 0.2MPa; S3. Room temperature ~ 150℃, applied pressure is 80MPa, 150℃ ~ 600℃ applied pressure is 10MPa, 600℃ ~ 1700℃ applied pressure is 30MPa, heating rate is 10℃ / min, and the holding time at the highest temperature is 2h; S4. Process the sintered ceramic into the shape of a high-frequency electric knife, load the ceramic electric knife onto the high-frequency generator, and adjust the output power for electric cutting. Example 3
[0024] The present invention provides an anti-adhesion medical high-frequency ceramic electric knife, and the specific preparation process includes: S1. Alumina ceramic powder, titanium nitride ceramic powder, magnesium oxide ceramic powder and 50nm zirconium oxide ceramic powder with a particle size of 500nm were mixed in a mass ratio of 58:30:2:10, n-hexane was added, ultrasonic stirring was performed for 20min, the mixture was put into a ball mill, and ball milling was performed for 24h. The ball-milled ceramic powder was dried and sieved with a 400-mesh sieve to obtain dry powder; S2. The dry powder was loaded into a mold, 1wt% of the dry powder mass of a mixed organic acid was added, and hot-pressed sintering was performed under nitrogen pressure at a nitrogen pressure of 0.2MPa; S3. Room temperature ~ 150℃, applied pressure is 80MPa, 150℃ ~ 600℃ applied pressure is 10MPa, 600℃ ~ 1700℃ applied pressure is 30MPa, heating rate is 10℃ / min, and the holding time at the highest temperature is 2h; S4. Process the sintered ceramic into the shape of a high-frequency electric knife, load the ceramic electric knife onto the high-frequency generator, and adjust the output power for electric cutting. Example 4
[0025] The present invention provides an anti-adhesion medical high-frequency ceramic electric knife, and the specific preparation process includes: S1. Alumina ceramic powder with a particle size of 500nm, titanium nitride ceramic powder, magnesium oxide ceramic powder, and 50nm zirconium oxide ceramic powder were mixed in a mass ratio of 48:40:2:10, anhydrous ethanol was added, ultrasonic stirring was performed for 20min, the mixture was put into a ball mill, and ball milled for 24h. The ball-milled ceramic powder was dried and sieved with a 400-mesh sieve to obtain a dry powder; S2. The dry powder was loaded into a mold, 1wt% of the dry powder mass of a mixed organic acid was added, and hot-pressed sintering was performed under nitrogen pressure at a nitrogen pressure of 0.2MPa; S3. Room temperature ~ 150℃, applied pressure is 80MPa, 150℃ ~ 600℃ applied pressure is 10MPa, 600℃ ~ 1700℃ applied pressure is 30MPa, heating rate is 10℃ / min, and the holding time at the highest temperature is 2h; S4. Process the sintered ceramic into the shape of a high-frequency electric knife, load the ceramic electric knife onto the high-frequency generator, and adjust the output power for electric cutting. Example 5
[0026] The present invention provides an anti-adhesion medical high-frequency ceramic electric knife, and the specific preparation process includes: S1. Alumina ceramic powder with a particle size of 500nm, titanium nitride ceramic powder, magnesium oxide ceramic powder, and 50nm zirconium oxide ceramic powder were mixed in a mass ratio of 58:30:2:10, anhydrous ethanol was added, ultrasonic stirring was performed for 20min, the mixture was put into a ball mill, and ball milled for 24h. The ball-milled ceramic powder was dried and sieved with a 400-mesh sieve to obtain a dry powder; S2. The dry powder was loaded into a mold, 1wt% of the dry powder mass of a mixed organic acid was added, and hot-pressed sintering was performed under nitrogen pressure at a nitrogen pressure of 0.2MPa; S3. Room temperature ~ 150℃, applied pressure is 80MPa, 150℃ ~ 600℃ applied pressure is 10MPa, 600℃ ~ 1700℃ applied pressure is 30MPa, heating rate is 10℃ / min, and the holding time at the highest temperature is 2h; S4. Process the sintered ceramic into the shape of a high-frequency electric knife, load the ceramic electric knife onto the high-frequency generator, and adjust the output power for electric cutting. Example 6
[0027] The present invention provides an anti-adhesion medical high-frequency ceramic electric knife, and the specific preparation process includes: S1. Alumina ceramic powder with a particle size of 500nm, titanium nitride ceramic powder, magnesium oxide ceramic powder, and 50nm zirconium oxide ceramic powder were mixed in a mass ratio of 68:20:2:10, anhydrous ethanol was added, ultrasonic stirring was performed for 20min, the mixture was put into a ball mill, and ball milled for 24h. The ball-milled ceramic powder was dried and sieved with a 400-mesh sieve to obtain a dry powder; S2. The dry powder was loaded into a mold, 1wt% of the dry powder mass of a mixed organic acid was added, and hot-pressed and sintered under nitrogen pressure at a nitrogen pressure of 0.2MPa; S3. The applied pressure from room temperature to 600℃ is 10MPa, the applied pressure from 600℃ to 1700℃ is 30MPa, the heating rate is 10℃ / min, and the holding time at the highest temperature is 2h; S4. Process the sintered ceramic into the shape of a high-frequency electric knife, load the ceramic electric knife onto the high-frequency generator, and adjust the output power for electric cutting. Example 7
[0028] The present invention provides an anti-adhesion medical high-frequency ceramic electric knife, and the specific preparation process includes: S1. Alumina ceramic powder with a particle size of 500nm, titanium nitride ceramic powder, magnesium oxide ceramic powder, and 50nm zirconium oxide ceramic powder were mixed in a mass ratio of 48:40:2:10, anhydrous ethanol was added, ultrasonic stirring was performed for 15min, the mixture was put into a ball mill, and ball milled for 24h. The ball-milled ceramic powder was dried and sieved with a 400-mesh sieve to obtain a dry powder; S2. The dry powder was loaded into a mold, 1wt% of the dry powder mass of a mixed organic acid was added, and hot-pressed and sintered under nitrogen pressure at a nitrogen pressure of 0.2MPa; S3. The applied pressure from room temperature to 600℃ is 10MPa, the applied pressure from 600℃ to 1700℃ is 30MPa, the heating rate is 10℃ / min, and the holding time at the highest temperature is 2h; S4. Process the sintered ceramic into the shape of a high-frequency electric knife, load the ceramic electric knife onto the high-frequency generator, and adjust the output power for electric cutting. Example 8
[0029] The present invention provides an anti-adhesion medical high-frequency ceramic electric knife, and the specific preparation process includes: S1. Alumina ceramic powder with a particle size of 500nm, titanium nitride ceramic powder, magnesium oxide ceramic powder, and 50nm zirconium oxide ceramic powder were mixed in a mass ratio of 48:40:2:10, anhydrous ethanol was added, ultrasonic stirring was performed for 20min, the mixture was put into a ball mill, and ball milled for 24h. The ball-milled ceramic powder was dried and sieved with a 400-mesh sieve to obtain a dry powder; S2. The dry powder was loaded into a mold, 1wt% of the dry powder mass of a mixed organic acid was added, and hot-pressed and sintered under nitrogen pressure at a nitrogen pressure of 0.2MPa; S3. The applied pressure from room temperature to 600℃ is 10MPa, the applied pressure from 600℃ to 1700℃ is 30MPa, the heating rate is 10℃ / min, and the holding time at the highest temperature is 4h; S4. Process the sintered ceramic into the shape of a high-frequency electric knife, load the ceramic electric knife onto the high-frequency generator, and adjust the output power for electric cutting. Example 9
[0030] The present invention provides an anti-adhesion medical high-frequency ceramic electric knife, and the specific preparation process includes: S1. Alumina ceramic powder with a particle size of 500nm, titanium nitride ceramic powder, magnesium oxide ceramic powder, and 50nm zirconium oxide ceramic powder were mixed in a mass ratio of 48:40:2:10, anhydrous ethanol was added, ultrasonic stirring was performed for 20min, the mixture was put into a ball mill, and ball milled for 24h. The ball-milled ceramic powder was dried and sieved with a 400-mesh sieve to obtain a dry powder; S2. The dry powder was loaded into a mold, 1wt% of the dry powder mass of a mixed organic acid was added, and hot-pressed and sintered under nitrogen pressure at a nitrogen pressure of 0.2MPa; S3. The applied pressure from room temperature to 600℃ is 10MPa, the applied pressure from 600℃ to 1700℃ is 30MPa, the heating rate is 10℃ / min, and the holding time at the highest temperature is 6h; S4. Process the sintered ceramic into the shape of a high-frequency electric knife, load the ceramic electric knife onto the high-frequency generator, and adjust the output power for electric cutting. Example 10
[0031] The present invention provides an anti-adhesion medical high-frequency ceramic electric knife, and the specific preparation process includes: S1. Alumina ceramic powder with a particle size of 500nm, titanium nitride ceramic powder, magnesium oxide ceramic powder, and 50nm zirconium oxide ceramic powder were mixed in a mass ratio of 48:40:2:10, anhydrous ethanol was added, ultrasonic stirring was performed for 5min, the mixture was put into a ball mill, and ball milled for 24h. The ball-milled ceramic powder was dried and sieved with a 400-mesh sieve to obtain a dry powder; S2. The dry powder was loaded into a mold, 1wt% of the dry powder mass of a mixed organic acid was added, and hot-pressed and sintered under nitrogen pressure at a nitrogen pressure of 0.2MPa; S3. The applied pressure from room temperature to 600℃ is 10MPa, the applied pressure from 600℃ to 1700℃ is 30MPa, the heating rate is 10℃ / min, and the holding time at the highest temperature is 8h; S4. Process the sintered ceramic into the shape of a high-frequency electric knife, load the ceramic electric knife onto the high-frequency generator, and adjust the output power for electric cutting. Embodiment 11
[0032] The present invention provides an anti-adhesion medical high-frequency ceramic electric knife, and the specific preparation process includes: S1. Alumina ceramic powder with a particle size of 500nm, titanium nitride ceramic powder, magnesium oxide ceramic powder, and 50nm zirconium oxide ceramic powder were mixed in a mass ratio of 38:50:2:10, anhydrous ethanol was added, ultrasonic stirring was performed for 20min, the mixture was put into a ball mill, and ball milled for 24h. The ball-milled ceramic powder was dried and sieved with a 400-mesh sieve to obtain a dry powder; S2. The dry powder was loaded into a mold, 1wt% of the dry powder mass of a mixed organic acid was added, and hot-pressed sintering was performed under nitrogen pressure at a nitrogen pressure of 0.2MPa; S3. The applied pressure from room temperature to 600℃ is 10MPa, the applied pressure from 600℃ to 1700℃ is 30MPa, the heating rate is 10℃ / min, and the holding time at the highest temperature is 2h; S4. Process the sintered ceramic into the shape of a high-frequency electric knife, load the ceramic electric knife onto the high-frequency generator, and adjust the output power for electric cutting. Example 12
[0033] The present invention provides an anti-adhesion medical high-frequency ceramic electric knife, and the specific preparation process includes: S1. Alumina ceramic powder with a particle size of 500 nm, titanium nitride ceramic powder, carbon fiber staple, magnesium oxide ceramic powder, and 50 nm zirconium oxide ceramic powder were mixed in a mass ratio of 38:30:20:2:10, anhydrous ethanol was added, ultrasonic stirring was performed for 20 min, the mixture was put into a ball mill, and ball milled for 24 h. The ball-milled ceramic powder was dried and sieved with a 400-mesh sieve to obtain a dry powder; S2. The dry powder was loaded into a mold, 1wt% of the dry powder mass of a mixed organic acid was added, and hot-pressed sintering was performed under nitrogen pressure at a nitrogen pressure of 0.2MPa; S3. The applied pressure from room temperature to 600℃ is 10MPa, the applied pressure from 600℃ to 1700℃ is 20MPa, the heating rate is 10℃ / min, and the holding time at the highest temperature is 2h; S4. Process the sintered ceramic into the shape of a high-frequency electric knife, load the ceramic electric knife onto the high-frequency generator, and adjust the output power for electric cutting. Embodiment 13
[0034] The present invention provides an anti-adhesion medical high-frequency ceramic electric knife, and the specific preparation process includes: S1. Alumina ceramic powder, titanium nitride ceramic powder, graphene, magnesium oxide ceramic powder and 50nm zirconium oxide ceramic powder with a particle size of 500nm were mixed in a mass ratio of 38:30:20:2:10, anhydrous ethanol was added, ultrasonic stirring was performed for 20min, the mixture was put into a ball mill, and ball milled for 24h. The ball-milled ceramic powder was dried and sieved with a 400-mesh sieve to obtain a dry powder; S2. The dry powder was loaded into a mold, 1wt% of the dry powder mass of a mixed organic acid was added, and hot-pressed and sintered under nitrogen pressure at a nitrogen pressure of 0.2MPa; S3. The applied pressure from room temperature to 600℃ is 10MPa, the applied pressure from 600℃ to 1700℃ is 30MPa, the heating rate is 10℃ / min, and the holding time at the highest temperature is 2h; S4. Process the sintered ceramic into the shape of a high-frequency electric knife, load the ceramic electric knife onto the high-frequency generator, and adjust the output power for electric cutting. Embodiment 14
[0035] The present invention provides an anti-adhesion medical high-frequency ceramic electric knife, and the specific preparation process includes: S1. Silicon nitride ceramic powder, titanium nitride ceramic powder, carbon nanotubes, magnesium oxide ceramic powder and titanium carbonitride powder with a particle size of 500 nm were mixed in a mass ratio of 18:40:30:2:10, anhydrous ethanol was added, ultrasonic stirring was performed for 20 min, the mixture was put into a ball mill, and ball milled for 24 h. The ball-milled ceramic powder was dried and sieved with a 400-mesh sieve to obtain a dry powder; S2. The dry powder was loaded into a mold, 1wt% of the dry powder mass of a mixed organic acid was added, and hot-pressed and sintered under nitrogen pressure at a nitrogen pressure of 0.2MPa; S3. The applied pressure from room temperature to 600℃ is 10MPa, the applied pressure from 600℃ to 1700℃ is 30MPa, the heating rate is 10℃ / min, and the holding time at the highest temperature is 2h; S4. Process the sintered ceramic into the shape of a high-frequency electric knife, load the ceramic electric knife onto the high-frequency generator, and adjust the output power for electric cutting. Comparative Example 1
[0036] The present invention provides an anti-adhesion medical high-frequency ceramic electric knife, and the specific preparation process includes: S1. Alumina ceramic powder, titanium nitride ceramic powder, magnesium oxide ceramic powder and 50nm zirconium oxide ceramic powder with a particle size of 500nm were mixed in a mass ratio of 58:30:12:0, anhydrous ethanol was added, ultrasonic stirring was performed for 15min, the mixture was put into a ball mill, and ball milling was performed for 20h. The ball-milled ceramic powder was dried and sieved with a 400-mesh sieve to obtain a dry powder; S2. The dry powder was loaded into a mold, 1wt% of the dry powder mass of a mixed organic acid was added, and hot-pressed sintering was performed under nitrogen pressure at a nitrogen pressure of 0.2MPa; S3. Room temperature ~ 150℃, applied pressure is 80MPa, 150℃ ~ 600℃ applied pressure is 10MPa, 600℃ ~ 1700℃ applied pressure is 30MPa, heating rate is 10℃ / min, and the holding time at the highest temperature is 2h; S4. Process the sintered ceramic into the shape of a high-frequency electric knife, load the ceramic electric knife onto the high-frequency generator, and adjust the output power for electric cutting. Comparative Example 2
[0037] The present invention provides an anti-adhesion medical high-frequency ceramic electric knife, and the specific preparation process includes: S1. Alumina ceramic powder, titanium nitride ceramic powder, magnesium oxide ceramic powder and 50nm zirconium oxide ceramic powder with a particle size of 500nm are mixed in a mass ratio of 58:30:6:6, anhydrous ethanol is added, and the mixture is placed in a ball mill without ultrasonic stirring, and ball milled for 20h. The ball-milled ceramic powder is dried and sieved with a 400-mesh sieve to obtain a dry powder; S2. The dry powder was loaded into a mold, 1wt% of the dry powder mass of a mixed organic acid was added, and hot-pressed sintering was performed under nitrogen pressure at a nitrogen pressure of 0.2MPa; S3. Room temperature ~ 150℃, applied pressure is 80MPa, 150℃ ~ 600℃ applied pressure is 10MPa, 600℃ ~ 1700℃ applied pressure is 30MPa, heating rate is 10℃ / min, and the holding time at the highest temperature is 2h; S4. Process the sintered ceramic into the shape of a high-frequency electric knife, load the ceramic electric knife onto the high-frequency generator, and adjust the output power for electric cutting. Comparative Example 3
[0038] The present invention provides an anti-adhesion medical high-frequency ceramic electric knife, and the specific preparation process includes: S1. Alumina ceramic powder, titanium nitride ceramic powder, magnesium oxide ceramic powder and 50nm zirconium oxide ceramic powder with a particle size of 500nm are mixed in a mass ratio of 58:30:4:8, and n-hexane is added. Without ultrasonic stirring, the mixture is put into a ball mill and ball milled for 20h. The ball-milled ceramic powder is dried and sieved with a 400-mesh sieve to obtain a dry powder; S2. The dry powder is loaded into a mold and hot-pressed and sintered under nitrogen pressure at a nitrogen pressure of 0.2MPa; S3. Room temperature ~ ~ 1700℃, applied pressure is 10MPa, heating rate is 10℃ / min, and the holding time at the highest temperature is 2h; S4. Process the sintered ceramic into the shape of a high-frequency electric knife, load the ceramic electric knife onto the high-frequency generator, and adjust the output power for electric cutting. Comparative Example 4
[0039] The present invention provides an anti-adhesion medical high-frequency ceramic electric knife, and the specific preparation process includes: S1. Alumina ceramic powder, titanium nitride ceramic powder, magnesium oxide ceramic powder and 50nm zirconium oxide ceramic powder with a particle size of 500nm are mixed in a mass ratio of 78:10:2:10, anhydrous ethanol is added, and the mixture is placed in a ball mill without ultrasonic stirring, and ball milled for 20h. The ball-milled ceramic powder is dried and sieved with a 400-mesh sieve to obtain a dry powder; S2. The dry powder was loaded into a mold, 1wt% of the dry powder mass of a mixed organic acid was added, and hot-pressed and sintered under nitrogen pressure at a nitrogen pressure of 0.2MPa; S3. Room temperature ~ 150℃, applied pressure is 80MPa, 150℃ ~ 600℃ applied pressure is 10MPa, 600℃ ~ 1700℃ applied pressure is 30MPa, heating rate is 10℃ / min, and the holding time at the highest temperature is 2h; S4. Process the sintered ceramic into the shape of a high-frequency electric knife, load the ceramic electric knife onto the high-frequency generator, and adjust the output power for electric cutting. Comparative Example 5
[0040] A 316 stainless steel electric knife was used to measure the contact angle, electric cutting experiment and adhesion amount.
[0041] By observing the performance test results between the various embodiments, it can be found that due to the irregular morphology of titanium nitride particles, the ceramic powder that has not been ultrasonically stirred before ball milling is not easy to mix evenly. As shown in Comparative Example 2, its mechanical properties are significantly reduced after sintering, which is not conducive to subsequent grinding. By comparing Examples 1 to 4 with Comparative Example 1, the reduction of zirconium oxide will cause a significant reduction in bending strength, affecting subsequent processing and use, and is not conducive to the preparation of high-frequency electric knives of various shapes. By comparing Example 6 with Comparative Example 4, it can be found that when the conductive phase content is less than 20wt%, its AC impedance is too large and cannot be used as a high-frequency electric knife. By comparing Example 2 with Comparative Example 3, it can be found that step-by-step pressure sintering can obtain higher performance ceramics, which is conducive to sintering densification. By Comparative Example 5, it can be found that the water contact angle results of the traditional stainless steel electric knife show that the electric knife is hydrophilic, the amount of tissue adhesion after cutting is large, and through pathological section observation, the incision thermal damage is serious, which is not conducive to wound healing and scar recovery. Compared with the ceramic electric knife in Example 1, the incision is neat and the adhesion is low, which shows that the medical ceramic high-frequency electric knife provided by the present invention has specific lower thermal damage and lower adhesion. At the same time, a small amount of mixed organic acid is added. It is conducive to achieving better particle rearrangement under low temperature and high pressure conditions, which is helpful for the densification of ceramic sintering. It can be found from the test results of Examples 1 to 13 that the mass proportion of the conductive phase should be above 20wt% in order to play a better high-frequency current conduction role. Composite ceramics use a certain amount of toughening phase, and the toughening phase content is 2wt% to 10wt%.
[0042] Table 1 Example Bending strength Contact angle Cutting performance AC impedance Adhesion amount 1 412MPa 100.101° 5 4.9*10^-3Ω·cm 0.48% 2 421MPa 98.762° 4 4.4*10^-3Ω·cm 0.51% 3 431MPa 100.786° 5 5.1*10^-3Ω·cm 0.49% 4 466MPa 103.626° 5 7.97*10^-4Ω·cm 0.43% 5 412MPa 98.379° 4 5.3*10^-3Ω·cm 0.52% 6 348MPa 95.932° 4 6.35*10^-3Ω·cm 0.75% 7 434MPa 102.968° 4 8.22*10^-4Ω·cm 0.46% 8 422MPa 102.971° 5 8.04*10^-4Ω·cm 0.45% 9 430MPa 102.949° 5 9.62*10^-4Ω·cm 0.45% 10 426MPa 102.212° 5 8.64*10^-4Ω·cm 0.46% 11 358MPa 106.186° 5 4.6*10^-4Ω·cm 0.40% 12 564MPa 98.252° 4 9.26*10^-3Ω·cm 0.55% 13 480MPa 98.252° 4 8.99*10^-3Ω·cm 0.56% 14 669MPa 98.252° 4 5.51*10^-4Ω·cm 0.51% Comparative Example 1 299MPa 100.442° —— 6.6*10^-3Ω·cm —— Comparative Example 2 313MPa 99.021° 2 5.64*10^-3Ω·cm 0.54% Comparative Example 3 255MPa 99.674° —— 4.906*10^-3Ω·cm —— Comparative Example 4 325MPa 93.239° —— 6.837*10^12Ω·cm —— Comparative Example 5 —— 84.500° 1 —— 0.80%
Claims
1. A medical ceramic high-frequency electric knife, characterized by: S1. Mix the ceramic base phase, the conductive phase, the sintering aid and the toughening phase in a certain mass ratio, add anhydrous ethanol, first disperse them by ultrasonic stirring, then put them into a ball mill and mix them with spherical graphite, dry the ball-milled ceramic powder and sieve it with a sieve to obtain a dry powder; S2, after the dry powder is loaded into the mold, a certain mass of mixed organic acid is added, and hot pressing sintering is performed under nitrogen pressure; S3. During the heating process, different hydraulic pressures are set at room temperature to 150°C, 150°C to 600°C, and 600°C to 1700°C. When the temperature reaches the highest temperature, keep it warm for a certain period of time. S4. Process the sintered ceramic into the shape of a high-frequency electric knife, load the ceramic electric knife onto a high-frequency generator, and adjust the output power for electric cutting.
2. A medical ceramic high-frequency electric knife according to claim 1, characterized in that The ultrasonic stirring time is 5~20min.
3. A medical ceramic high-frequency electric knife according to claim 1, characterized in that The ceramic matrix phase is one or more of aluminum oxide, zirconium oxide and silicon nitride, and the sintering aid is one or more of magnesium oxide, silicon oxide and rare earth oxide.
4. A medical ceramic high-frequency electric knife according to claim 1, characterized in that after the dry powder is loaded into the mold, the mass ratio of the mixed organic acid added is 0.3wt~1wt% of the mass of the powder.
5. A medical ceramic high-frequency electric knife as described in claim 1, characterized in that the hydraulic pressure during the heating process is set to 10-80MPa at room temperature-150°C and 20-30MPa at 600°C-1700°C.
6. The method for preparing a medical ceramic high-frequency electric knife according to claim 1, characterized in that the temperature is kept at a maximum temperature for a time of 2 to 8 hours.
7. A medical ceramic high-frequency electric knife as described in claim 1, characterized in that the conductive phase is one or more of titanium nitride, titanium carbide, titanium dioxide, graphene, graphene oxide, and carbon nanotubes, and the mass proportion of the conductive phase is 20wt%~70wt%.
8. The medical ceramic high-frequency electric knife according to claim 1, characterized in that The toughening phase is one or more of zirconium oxide, carbon fiber, carbon nanotube, and titanium carbonitride, and the mass proportion of the toughening phase is 2wt%~10wt%.
Citation Information
Patent Citations
Conductive method for zirconia ceramic surface
CN112979346A
Zirconium boride-based conductive ceramic material and preparation process thereof
CN118754674A
A method for preparing conductive ceramic with controllable resistivity
CN118812248B
Preparation method of silicon nitride ceramic blade
CN101850502A
Silicon nitride compound phase ceramic knife tool material with whiskers for supplementing toughness and strength
CN1051900A